Uji Kinerja Alat Penghancur Kohe Kambing Tipe Basah - Aldi Saputra; Budianto Lanya; Siti Suharyatun; Agus Haryanto (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2021)
Goat manure is one of the manure which is widely used in agriculture. Due to its hard physical nature, goat manure needs to be crushed before being applied to facilitate the decomposition process. Currently, there is a wet type of goat dung grinder or crusher used by the community. This study aims to test the performance of the goat manure crusher based on the engine rotation speed (rpm). The research was conducted using 3 different rotation speed of the blade shaft, namely 968 rpm, 1208 rpm, 1454 rpm. The experiment parameters included working capacity, fuel consumtion, and degree of crushing. The results showed that the wet type goat manure crusher had the best working capacity at 1208 rpm blade rotation with 255,78 kg/h working capacity, 1.43 lt/h fuel consumption, and 99.3% crushing uniformity. Keywords: manure, rpm, wet goat manure crusher